THE INFLUENCE OF RICE CULINARY CONSUMPTION VALUES ON TOURIST EXPERIENCE IN CIAYUMAJAKUNING - Anissa Aulia Rahmasari; Galih Kusumah (RADJA PUBLIKA, 2025)
This study investigates how tourist perceptions of local food consumption values influence their attitudes, destination food image, and behavioral intentions within the Ciayumajakuning region of Indonesia. Drawing on the Value Attitude Behavior (VAB) model and using Structural Equation Modeling (SEM) with a sample of 225 respondents, the study finds that taste/quality, emotional, and epistemic values significantly influence attitudes toward local food, which in turn shape food destination image and intention to revisit or recommend. Conversely, health, price, and social values showed no significant impact. The findings highlight the primacy of experiential and affective dimensions in culinary tourism and offer both theoretical refinement to the VAB model and practical insights for destination marketers.